Validated Chromatography Method for Analysis of Formaldehyde Migration Levels in Bottled Drinking Water - Ramadhani, Nur; Yulianty, Risfah; Rifai, Yusnita; Aswad, Muhammad; Alam, Gemini; Naid, Tadjuddin; Kasim, Athia Kurnia (Science and Technology Indonesia, 2024)
Polyethylene terephthalate (PET) is utilized in the containment of potable water, nonetheless, it is susceptible to impairment due to temperature and duration of storage. Migration of formaldehyde from PET arises as a consequence of thermal deterioration. This study aims to ascertain the extent of formaldehyde transference in PET-contained drinking water of varying condition, subjected to diverse temperature setting and storage durations. An examination into the levels of formaldehyde migration in polyethylene terephthalate (PET) bottled drinking water was effectively carried out employing a validated high-performance liquid chromatography (HPLC) technique. A total of 162 water samples from three different PET bottled water brands sourced from supermarkets in Palu City, Central Sulawesi, Indonesia, underwent analysis. The formaldehyde assessment was executed utilizing a mobile phase composition of methanol:acetonitrile:water (48:12:40 v/v) for 12.97 minutes at a flow rate of 0.8 mL/minute on the 1st day, the 14th day, and the 42nd day while stored at room temperature and exposed to sunlight. Formaldehyde, lacking effective chromophoric entities and not readily ionizable, necessitated derivatization with 2,4-dinitrophenylhydrazine before HPLC analysis. The findings of the study demonstrated exceptional method linearity within the concentration span of 0.5 to 1321 µg/mL, exhibiting a commendable correlation coefficient of 0.999. The limit of detection (LOD) and quantification (LOQ) were determined to be 17.33 and 57.76 µg/mL, correspondingly. Precision evaluations displayed average intraday and interday values of 128.46±3.48% and 103.19±0.12%, respectively (%RSD < 2/3 CV Horwitz ratio). The intraday and interday %recovery values were computed at 97.22±3.48% and 96.83±0.14% (n = 6). The scrutiny of formaldehyde concentrations in the water samples unveiled the absence of formaldehyde migration.